Passive immunisation of European seabass (Dicentrarchus labrax) against Nervous Necrosis Virus (NNV) - Abrantes, Catarina Rebelo (2024)
Viral infections in aquaculture are one of the main obstacles to aquaculture development, as they cause high economic losses. Viral encephalopathy and retinopathy (VER), caused by nervous necrosis virus (NNV), significantly impacts marine and freshwater aquaculture, causing high mortality in larval and juvenile populations with mortality rates up to 100%. There is no effective treatment against this infection nor commercial vaccine development. This study aimed to assess the applicability of a polyclonal antibody with antiviral potential for supplementing the diet of European seabass (Dicentrarchus labrax) in the larval stage after contact with NNV of the RGNNV genotype, as well as to evaluate how this antibody treatment could influence both fish survival rates and the reduction of viral replication over time. A neutralisation protocol was established using rabbit anti-NNV polyclonal antibodies as a positive control. Results demonstrate that PAb can be effectively administered to fish through both immersion and dietary routes, with findings suggesting potential protective effects when delivered via the diet. It was found that NNV infection is more efficient via injection (20%) compared to immersion (0%). Mortality was monitored and analysed throughout the trial, along with viral load, to gain a comprehensive understanding of the potential benefits associated with the administration of this polyclonal antibody following NNV infection. A reduction in mortality was observed in the treatment in which the feed was supplemented with rabbit serum (33.2%) compared to the treatment where the fish were infected with NNV (41.7%). A reduction in viral load was also observed between these treatments. Thus, supplementation with antiviral immunostimulants could be a promising strategy to prevent irreversible damage. However, more studies are still needed to understand how the immune system works in the presence of NNV with subsequent supplementation with polyclonal antibodies.